Institutional Decay in Zimbabwe's Local Authorities: Insights from the Auditor-General' s Reports - Zvoushe, Hardlife (Journal of Economic Development, Environment and People, 2026)
Abstract: Public sector organisations in Zimbabwe have been showing deepening signs of institutional decay over the years, characterised by a gradual erosion of effectiveness, integrity, and capacity. This paper specifically examines the pervasive issue of institutional decay within Zimbabwe’s local governments, utilising findings from the Auditor General’s (AG) reports. Evidence for demonstrating the occurrence of institutional decay was gathered using unobtrusive research techniques, mainly documentary analysis and reviews of publicly available reports of the Auditor-General. Findings indicate that institutional decay at the subnational tier of government is evident in widespread financial mismanagement, governance irregularities, and severe failures in service delivery. By synthesising the recurring audit observations, this paper demonstrates how these systemic deficiencies undermine the core functions of local authorities, leading to a significant disconnect between their mandate and their operational reality, ultimately impacting the well-being of citizens.